Migratory phase of Litomosoides sigmodontis filarial infective larvae is associated with pathology and transient increase of S100A9 expressing neutrophils in the lung. - Gregory Karadjian; Frédéric Fercoq; Nicolas Pionnier; Nathaly Vallarino-Lhermitte; Emilie Lefoulon; Adélaïde Nieguitsila; Sabine Specht; Leo M Carlin; Coralie Martin (PLoS Neglected Tropical Diseases)
Filarial infections are tropical diseases caused by nematodes of the Onchocercidae family such as Mansonella perstans. The infective larvae (L3) are transmitted into the skin of vertebrate hosts by blood-feeding vectors. Many filarial species settle in the serous cavities including M. perstans in humans and L. sigmodontis, a well-established model of filariasis in mice. L. sigmodontis L3 migrate to the pleural cavity where they moult into L4 around day 9 and into male and female adult worms around day 30. Little is known of the early phase of the parasite life cycle, after the L3 is inoculated in the dermis by the vector and enters the afferent lymphatic vessels and before the moulting processes in the pleural cavity. Here we reveal a pulmonary phase associated with lung damage characterized by haemorrhages and granulomas suggesting L3 reach the lung via pulmonary capillaries and damage the endothelium and parenchyma by crossing them to enter the pleural cavity. This study also provides evidence for a transient inflammation in the lung characterized by a very early recruitment of neutrophils associated with high expression levels of S100A8 and S100A9 proteins.